End of Vietnam War Discussed by Local Activists - Spartan Daily:::::::::
When the war ended, local activists, including the coordinator of San José State University's Young Socialist Alliance John Hummer, reflected on the impact of the anti-war protests. (Spartan Daily, May 7, 1975)